Physiological Characteristics of Soybean Leaves with and without Shading at Palm Oil Plantation, West Papua - Alce Ilona Noya; Nouke L. Mawikere; Purbo Kurniawan; Deasy Mayawati (Department of Crop Science, Faculty of Agriculture, Andalas University, 2019)
The objective of this research was to identify several leaf physiological characteristics of three soybean varieties with and without shading f Oil Palm Plantation. The research was carried out in the oil palm plantation area of PT. Medcopapua Hijau Selaras, Prafi District, West Papua from June to August 2018. This study used a Randomized Complete Design with three replications on two environmental conditions (shade and without shade). The second factor is soybean varieties, consisting of Detam 1, Demas 1 and Dena 1. Leaf samples were collected at seven weeks after planting. The result indicated that no interaction between environmental conditions and varieties on the content of chlorophyll a, chlorophyll b, the ratio of chlorophyll a/b, chlorophyll total, anthocyanin and leaf carotenoid. Conditions without shade increase chlorophyll b by 0.1334 mg/g compared to shaded. The Dena 1 variety has the highest chlorophyll a,b and chlorophyll total (1.1039,0.5587 and 1.6627 mg/g). All soybean varieties were not shown differences of anthocyanin or carotene leaves.